‘It’s a Dance Between Managing Both’: a qualitative study exploring perspectives of persons with knee osteoarthritis and type 2 diabetes mellitus on the impact of osteoarthritis on diabetes management and daily life - Crystal MacKay; Noah M Ivers; Janet A Parsons; Alanna Weisman; Gillian Hawker; Lorraine L Lipscombe; Lauren K King; Esther Waugh; Ian Stanaitis; Jane Stretton (BMJ Open, 2022)
Objectives Type 2 diabetes (T2DM) and knee osteoarthritis (OA) commonly co-occur and epidemiologic studies suggest concomitant symptomatic knee OA increases the risk of T2DM complications. We sought to explore the experiences and perspectives of individuals’ living with both symptomatic knee OA and T2DM, with a focus on the impact of OA on T2DM management and daily life.Design We conducted qualitative semistructured telephone interviews with persons living with T2DM and knee OA. We inductively coded and analysed interview transcripts, informed by interpretative description.Setting We recruited participants from a community arthritis self-management programme and an academic hospital’s family medicine clinic in Ontario, Canada.Participants We included 18 participants who had a physician diagnosis of both T2DM and knee OA, with variation age, gender, and duration of T2DM and knee OA.Results Participants with T2DM described how concomitant painful and disabling knee OA made it difficult to engage in physical activity, negatively impacting blood glucose control. Joint pain itself, associated sleep disturbance and emotional distress were also seen to affect blood glucose control. Beyond diabetes management, the impact of OA-related pain and functional limitations on nearly all aspects of daily life led participants to view their OA as important. Despite this, many participants described that their health professionals paid little attention to their OA, which left them to self-manage. Balancing both conditions also required navigating a medical system that provided piecemeal care.Conclusions Individuals with T2DM view symptomatic knee OA as an important barrier to both T2DM management and overall well-being, yet are frequently met with insufficient support from health professionals. Greater recognition and management of knee OA in persons with T2DM could help improve patient-centred care and potentially disease outcomes.